Outcomes of minimally invasive sleeve resection - Caso, Raul; Watson, Thomas J.; Khaitan, Puja G.; Marshall, M. Blair (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
Background: Sleeve resection allows for preservation of lung parenchyma and improved long-term outcomes when compared with pneumonectomy. Little is known about minimally invasive sleeve resection, especially indications, feasibility, technical aspects, complications, and outcomes. We reviewed our institutional experience with sleeve resections via a minimally invasive approach. Methods: We performed a retrospective review of a prospectively maintained database from 01/01/2010 to 11/01/2017. Indications, operative details, pathology, postoperative complications were reviewed and longer-term follow-up was reviewed. Results: Fifteen patients were identified (5 males, 10 females). Details are presented in Table 1. Patients ranged in age from 7 to 82 years (median, 57 years). Approaches included video-assisted thoracoscopic surgery (VATS) and robotic. Airway sleeve resection was performed in all patients with an additional arterioplasty in 4, one patient having a double sleeve. Length of stay ranged from 3 to 10 days (median, 5 days). Indication for surgery included carcinoid in 5 (1 atypical), NSCLC in 6, and 4 additional pathologies. Complications occurred in 6 patients: air leak [2], pericardial effusion [1], transient brachial plexopathy [1], and atrial fibrillation [2]. There were no anastomotic complications. Median follow-up was 4.2 years. There were no anastomotic strictures. Conclusions: In experienced centers, sleeve resection via a minimally invasive approach is feasible with acceptable morbidity and mortality. Results in this small series appear comparable with the open approach.